Meningkatkan Keterlibatan Siswa Madrasah Tsanawiyah dalam Pembelajaran Fiqih melalui Model Pembelajaran Kooperatif - Leni Nuraeni (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The implementation of the Independent Curriculum in Indonesia has encouraged various innovations in learning methods, including in the Fiqh subject at the Madrasah Tsanawiyah level. The cooperative learning model is one approach that is considered effective in improving conceptual understanding, students' application skills, and supporting the strengthening of the Pancasila Student Profile. This study aims to examine the implementation of the cooperative learning model in the Fiqh subject at MTs Al Jihadiyah, with a focus on challenges, supporting factors, and its impact on student learning outcomes. The method used is a qualitative approach with a case study design. Data collection techniques include participatory observation, in-depth interviews with teachers and students, and analysis of learning documents. Data were analyzed thematically with triangulation techniques to ensure the validity of the findings. The results of the study indicate that the implementation of the cooperative learning model is able to increase student active involvement and understanding of the Fiqh material. Some of the challenges faced include limited learning time and differences in student abilities. The supporting factors for the success of the implementation of this model include support from the school and training for teachers. Other positive impacts are seen in improving students' application skills in daily life and strengthening character according to the dimensions of the Pancasila Student Profile, especially in the aspects of collaboration and critical thinking.